Oral Treatments With Probiotics and Live Salmonella Vaccine Induce Unique Changes in Gut Neurochemicals and Microbiome in Chickens - Redweik, Graham A. J.; Daniels, Karrie; Severin, Andrew J.; Lyte, Mark; Mellata, Melha (Frontiers in Microbiology, 2020)
Cross-talk between the gut microbiota and neurochemicals affects health and well-being of animals. However, little is known about this interaction in chickens despite their importance in food production. Probiotics and live Salmonella vaccines are microbial products commonly given orally to layer pullets to improve health and ensure food safety. This study’s objective was to determine how these oral treatments, individually or in combination, would impact the gut environment of chickens. White Leghorn chicks were either non-treated (CON) or orally given probiotics (PRO), a recombinant attenuated Salmonella vaccine (RASV; VAX), or both (P+V). Birds were fed with probiotics daily beginning at one-day-old and orally immunized with RASV at four-days-old and boosted two weeks post-primary vaccination. At five weeks, ceca content, ceca tissues, and small intestinal scrapings (SISs) were collected from ten birds/group post-euthanasia for analyses. Catecholamine, but not serotonergic, metabolism was affected by treatments. Dopamine metabolism, indicated by L-DOPA and DOPAC levels, were increased in P+V birds versus CON and PRO birds. Based on 16S sequencing, beta diversity was more similar among vaccinated birds versus birds given probiotics, suggesting live Salmonella vaccination has a major selective pressure on microbial diversity. Abundances of Akkermansia muciniphila and Enterobacteriaceae positively correlated with levels of tyrosine and norepinephrine, respectively. Both enumeration and 16S sequencing, determined that PRO exhibited the greatest levels of Enterobacteriaceae in the ceca and feces, which was associated with greater IgA production against E. coli virulence factors as tested by ELISA. In summary, we demonstrate that using probiotics alone versus in combination with a live vaccine has major implications in catecholamine production and the microbiota of layer pullets. Additionally, unique correlations between changes in some neurochemicals and specific bacteria have been shown.